(3GdEYdGe GdQbejs (3GdGSJNOGeGJ hGdJCKjQGJs - (3gGTe, QHGH YHO GdQMefs ((3GdbGgQIs (3GdOGQ GdeUQjI GddHfGfjIs, 2023)
(3jTgO YGdefG Gdjhe KhQI MbjbjI aj eLGd GdEYdGe, KhQI CMOKJgG GdJcfhdhLjG GdQbejI(B. (3aGdEYdGe GdQbej HeNJda COhGJg hbfhGJI, GOi Edi JZjjQ LPQj aj WQb LeY GdCNHGQ hGdeYdheGJ, hEfJGL GdeMJhi GdEYdGej hfTQg, hjVja gPG GdcJGH dHfI eYGUQI LOjOI dHfGA GdecJHI GdYQHjI GdeYfjI HJWhQGJ GdEYdGe GdeYGUQs
Keywords: (3GdEJUGds; (3GdEYdGe GdQbejs; (3GdEYdGes